Kirk Ormand, Exchange and the Maiden. Mariage in Sophoclean Tragedy, University of Texas Press, Austin, 1999, X + 219 pp., ISBN 0-292-76051-5 (alk. paper), ISBN 0-292-76052 (pbk: alk paper) (Minerva, 2019)
Review: Kirk Ormand, Exchange and the Maiden. Mariage in Sophoclean Tragedy, University of Texas Press, Austin, 1999, X + 219 pp., ISBN 0-292-76051-5 (alk. paper), ISBN 0-292-76052 (pbk: alk paper)